The Use Of Graphic Calculators In Malaysian Secondary Schools:Students Perception And Teachers Constraints. - Hasan, Husna; Azizan, Munawir; Kassim, Suraiya (2005)
Graphic calculators were introduced into the Malaysian New Curriculum for Secondary Schools to enhance the quality of teaching and leaming of mathematics in the classrooms.